2018
DOI: 10.7150/jca.22355
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MICAL2, a novel tumor-promoting factor, accelerates tumor progression through regulating cell proliferation and EMT

Abstract: Molecule interacting with CasL 2 (MICAL2), a microtubule associated monooxygenase, is involved in cell growth, axon guidance, vesicle trafficking and apoptosis. Recent studies have demonstrated that MICAL2 is highly expressed in tumor and accelerates tumor progression and it is deemed to be a novel tumor-promoting factor. MICAL2 overexpression increases cell proliferation to accelerate tumor growth, and MICAL2 also promotes epithelial-mesenchymal transition (EMT)-related proteins to increase cancer cell metast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…Our previous work has reported that MICAL2 is the major regulator of breast cancer cell migration through inhibiting EGFR/P38 signalling activation . In the current study, we further extended our observation on MICAL‐L2 that lacks flavoprotein monooxygenase (MO) domain and owns C‐terminal domains (CTD) compared with MICAL2 . We showed that gastric cancer cell migrative potential was greatly impaired, which was likely mediated by the knockdown of MICAL‐L2 expression, whereas overexpression of MICAL‐L2 increased cell motility.…”
Section: Discussionsupporting
confidence: 69%
“…Our previous work has reported that MICAL2 is the major regulator of breast cancer cell migration through inhibiting EGFR/P38 signalling activation . In the current study, we further extended our observation on MICAL‐L2 that lacks flavoprotein monooxygenase (MO) domain and owns C‐terminal domains (CTD) compared with MICAL2 . We showed that gastric cancer cell migrative potential was greatly impaired, which was likely mediated by the knockdown of MICAL‐L2 expression, whereas overexpression of MICAL‐L2 increased cell motility.…”
Section: Discussionsupporting
confidence: 69%
“…Molecule interacting with CasL (MICAL2), a microtubule associated monooxygenase, is involved in cell growth, axon guidance, vesicle trafficking and apoptosis. Recent studies have demonstrated that MICAL2 is highly expressed in tumor and accelerates tumor progression and it is deemed to be a novel tumor-promoting factor [48,49]. PCSK5 belongs to the subtilisin-like proprotein convertase family.…”
Section: Discussionmentioning
confidence: 99%
“…The nine leading edge genes (Table 1) in GO: 0016705 had various roles ranging from cell proliferation (MICAL2) [46] to encoding enzymes for proper peroxisome function (PYPH) [47]. Four leading edge genes influence the ovarian (DBH, MICAL2, CYP19A1) and uterine environments (PTGS1), while one (HMOX1) is involved in the immune response ( Table 1).…”
Section: Plos Onementioning
confidence: 99%